2019
DOI: 10.1103/physrevlett.122.221601
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Results for the Lightest Bound States in N=1 Supersymmetric SU(3) Yang-Mills Theory

Abstract: The physical particles in supersymmetric Yang-Mills theory (SYM) are bound states of gluons and gluinos. We have determined the masses of the lightest bound states in SU(3) N = 1 SYM. Our simulations cover a range of different lattice spacings, which for the first time allows an extrapolation to the continuum limit. Our results show the formation of a supermultiplet of bound states, which provides a clear evidence for unbroken supersymmetry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…The N -ality dependence of confining string tensions is a probe of the confinement mechanism [51] and could be compared with studies of confining string tensions in both analytic and lattice setups [50,[52][53][54][55][56][57]. Further, our observation of the ∆ (as opposed to Y) shape of excited heavy baryons in SYM, should it extend to the theory on R 4 , could be viewed as a prediction for the nature of SYM heavy baryons and could be checked in future lattice simulations of SYM, as in [58][59][60]. We also note that the nature of DWs, of deconfinement on their worldvolume, and of confining strings has not been addressed in detail in other classes of theories to which similar considerations apply, such as nonsupersymmetric dYM and QCD(adj) on R 3 × S 1 .…”
Section: Future Workmentioning
confidence: 88%
“…The N -ality dependence of confining string tensions is a probe of the confinement mechanism [51] and could be compared with studies of confining string tensions in both analytic and lattice setups [50,[52][53][54][55][56][57]. Further, our observation of the ∆ (as opposed to Y) shape of excited heavy baryons in SYM, should it extend to the theory on R 4 , could be viewed as a prediction for the nature of SYM heavy baryons and could be checked in future lattice simulations of SYM, as in [58][59][60]. We also note that the nature of DWs, of deconfinement on their worldvolume, and of confining strings has not been addressed in detail in other classes of theories to which similar considerations apply, such as nonsupersymmetric dYM and QCD(adj) on R 3 × S 1 .…”
Section: Future Workmentioning
confidence: 88%
“…Therefore, only one (excited) contribution has been determined with a value between 0.7 and 1.5 in lattice units, depending on the number of stout smearing steps. In [17,24] it was reported that the lowest state of the pseudoscalar glueball is comparable with the first excited states of mesonic states and the gluino-glue. This agrees with our observations.…”
Section: Glueballsmentioning
confidence: 95%
“…More recently the spectrum of the low lying bound states [24] and supersymmetric Ward identities [25] have been calculated for N = 1 SYM with gauge group SU (3). Besides these studies with Wilson fermions, first investigations and simulations with domain wall fermions and overlap have been presented in [26][27][28] and [29,30].…”
Section: Jhep01(2021)154mentioning
confidence: 99%
See 1 more Smart Citation
“…Independent lattice calculations of the N =1 SYM theory with an untwisted lattice action are performed by the DESY-Münster collaboration. Their investigations cover the spectrum for gauge group SU(3) [7,8], variational analysis of the SU(2) spectrum [9,10] and the chiral symmetry in thermal SU(2) N = 1 SYM theory using the gradient flow [11,12].…”
Section: Lattice Formulation With a Twistmentioning
confidence: 99%